Pemaknaan Jabatan Karyawan dalam Struktur Organisasi: Studi Kualitatif terhadap Persepsi Karyawan PT. Surya Toto Indonesia Jakarta - Waluyani, Dyah Oktabriawatie; Dalianti, Indana; Mansur, Mansur; Prayogi, Munawir; Supratikta, Hadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
In organizational settings, job positions are often viewed not only as formal roles with defined responsibilities but also as symbols of personal identity, career progression, and individual achievement. This study aims to explore how employees perceive and interpret the positions they hold within the organizational structure, particularly in the context of PT. Surya Toto Indonesia Tbk. The research was conducted using a qualitative approach with descriptive analysis to gain deeper insights into employees’ experiences, perceptions, and expectations related to their roles. Data were collected through in-depth interviews with 10 employees from various hierarchical levels within the company. Respondents were selected using purposive sampling, based on predetermined criteria relevant to the study’s objectives. The findings indicate that a job position is not merely seen as a formal duty but also carries personal significance, including a sense of pride, validation, and a pathway for professional growth. However, several respondents also revealed that their positions often come with psychological burdens, such as high performance expectations, complex responsibilities, and persistent pressure to maintain standards. Moreover, workplace social dynamics may contribute to interpersonal conflicts or competition, which can adversely affect emotional well-being. These findings highlight the dual nature of organizational roles, encompassing both opportunities and challenges.